Effect of Temperature and Humidity on the Visibility of Mirage on the Runway of Sultan Iskandar Muda Airport, Aceh, Indonesia - Nasrullah Idris; Maswati Maswati; T. N. Usmawanda; Arlin Maya Sari (Journal of Physics and Its Applications, 2019)
The relationship between temperature and humidity of the environment with visibility of mirage has been studied by observing mirage on the runway of Sultan Iskandar Muda International Airport (SIM) Aceh, Indonesia. Temperature and humidity data were obtained from the Blang Bintang Meteorological Station database, Aceh Besar, Aceh, Indonesia. The observation shows that the mirage has been found since 07.00 AM in the morning until the afternoon at 18.00 PM, even until sunset. Mirage is also still visible when the weather is cloudy or drizzling, but disappears when heavy rain. The lowest and highest temperatures where the mirage can still be observed are 26 0C and 32 0C, respectively. Meanwhile, the lowest and highest air humidities where mirages can still be observed are 51 % and 92 %, respectively. Observation shows that changes in temperature and humidity in the runway environment greatly affect the appearance and visibility of mirages. When the air temperature is high and the humidity is low, the mirage appears with high visibility (very thick), so that it can be observed clearly. Conversely, when the air temperature is low and the humidity is high, the mirage appears with low visibility (very thin) or almost non-existent or completely gone